1993
DOI: 10.1002/pc.750140208
|View full text |Cite
|
Sign up to set email alerts
|

Fiber mat deformation in liquid composite molding. I: Experimental analysis

Abstract: When a resin in injected into the mold in liquid composite molding, the preplaced fiber mat may deform near the inlet gate because of the high momentum carried by the injected fluid. A fiber free region near the gate followed by the fiber mat deformation may emerge. This phenomenon is most likely to occur when the stacked fiber mats have low permeability and the resin has high viscosity. A set of mold filling experiments were carried out using an instrumented metal mold and a small transparent mold to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Because the fiber mats were compress ible, when the initial injection pressure was higher than the clamping pressure, the impact of injection caused the fiber mat to consolidate and further increased the pressure rise. Mat consolidation also resulted in a channel near the inlet, which reduced the flow resistance and the injection pressure (22). As the injection proceeded, these combined effects tended to keep the inlet pressure nearly constant, instead of increasing as predicted by simulation.…”
Section: Three-dimensional Mold Filling Simulationmentioning
confidence: 85%
See 1 more Smart Citation
“…Because the fiber mats were compress ible, when the initial injection pressure was higher than the clamping pressure, the impact of injection caused the fiber mat to consolidate and further increased the pressure rise. Mat consolidation also resulted in a channel near the inlet, which reduced the flow resistance and the injection pressure (22). As the injection proceeded, these combined effects tended to keep the inlet pressure nearly constant, instead of increasing as predicted by simulation.…”
Section: Three-dimensional Mold Filling Simulationmentioning
confidence: 85%
“…Impregnation-pressure-induced permeability change should be taken into account in the mold filling prccess. In SRIM processes, it has been reported that a dry spot formed near the inlet when a high resin flow rate was applied (22). This is a n extreme case resulting from the flow-induced fiber mat consolidation.…”
Section: Effect Of Fiber Mat Consolidation On Trans-plane Permeabilitymentioning
confidence: 99%
“…A brief startup period is observed in which curve fits do not match measured pressure values due to hose bulging and possibly inlet effects, especially at higher volume fraction. It has been shown that mat deformation at the inlet gate may have considerable effect on fill pressure [41,42], which may also contribute to the observed startup effects. Deviation in pressure from the theoretical values at the startup is minimized by reinforcing the hose leading to mold inlet and reducing the total hose length.…”
Section: Permeability Resultsmentioning
confidence: 99%
“…However, several papers show or qualitatively describe deformation of the solid preform [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19] (see also [20] for a recent review of the subject).…”
Section: Introductionmentioning
confidence: 99%